Resistência a acetamiprido de Lipaphis pseudobrassicae ( Davis) (Hemipetra: Aphididae) resistentes e suscetíveis ao parasitoide Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae, Aphidiinae) - Silva, Paula de Freitas (2016)
The aphid Lipaphis pseudobrassicae (Davis) has been shown low parasitism to parasitoid Diaeretiella rapae (Mc’Intosh) in Uberlândia region, probably due to secondary endosymbionts association. These symbionts can provide adaptive advantages to aphids such as increased resistance to parasitoids and heat. Moreover, symbionts can increase the production of cytochrome P450, which is the main enzyme on degradation of insecticides. Therefore, the objective of this study was to evaluate the resistance relationship of L. pseudobrassicae to the parasitoid D. rapae with the resistance to acetaprimid insecticide. This was done in order to verify if the resistance to parasitoid can increase the resistance to insecticide. To do so, the lethal dose of acetamiprid to kill 50% of the individuals (LD50 ) and the fecundity of the insects submitted to insecticide application were evaluated for aphids resistant and susceptible to parasitoid. We used four groups of L. pseudobrassicae collected in Uberlândia, MG. The first two groups were formed, respectively, by individuals of the same clone (C1), resistant (C1R) and susceptible (CIS) to parasitoid. The third group was formed by resistant individuals of a clone collected in canola (C2R) and the fourth group was formed by individuals from a population of commercial farming of cabbage (P1). To determine the LD50 we used 30 individuals of each aphid group, separated in three repetitions of 10 insects, which were submitted to dose-response trials with five concentration of acetaprimid insecticide (0.01, 0.1, 1, 10 and 100 ng. i.a/aphid). Besides, a control treatment using only acetone was done. The mortality and the number of nymphs produced 72 hours after the product application were observed and the LD50 was determined. There was no difference to LD50 for individuals of the same clone, C1R and C1S (0,06 e 0,06 ng. ia./aphid, respectively). The clone C2R showed the highest LD50 (0,14 ng. i.a/aphid) and P1 had the lowest (0,01 ng. i.a/aphid). Analogously, fecundity of C2R clones was the highest one while P1 had the lowest. The individuals of the same clone C1 did not show any difference on the number of nymphs produced. Thus, it cannot be assumed that resistance to the parasitoid is associated with resistance to the insecticide and the chemical control with acetaprimid is an option for controlling L. pseudobrassicae resistant to parasitoid D. rapae.